Application of Different Continuous Renal Replacement Therapy Hemofilter in Patients with Septic Shock Complicated with Acute Renal Injury - Shanqing Liu; Quanxia Cao; Rui Sun; Nan Wang (Tehran University of Medical Sciences, 2022)
Background: We aimed to compare the clinical effects of continuous renal replacement therapy (CRRT) with different hemofilters in patients with septic shock and acute kidney injury (AKI). Methods: Thirty patients with septic shock complicated with AKI admitted to The Fourth Affiliated Hospital of Anhui Medical University from 2018-2020 were selected and divided into the control and observation groups. The control group was treated with CRRT using the conventional ST-100 hemofilter. The observation group was treated with CRRT using the oXiris hemofilter for 48 hours, followed by CRRT with the conventional ST-100 hemofilter. Infection indexes, sepsis-related organ failure assessment (SOFA), changes in corresponding organ function indexes, duration of each treatment, and death were compared between the two groups during CRRT. Results: The white blood cells (WBC) count, high-sensitivity C-reactive protein (hs-CRP), and procalcitonin (PCT) levels were significantly decreased in the oXiris group 48 hours after CRRT (P= 0.048, 0.036, 0.031, respectively). After 48 hours of CRRT, SOFA score, serum lactic acid, and norepinephrine dose in the oXiris group were significantly lower than those in the control group (P= 0.039, 0.002, 0.021, respectively). The use time of vasoactive drugs and the treatment time of CRRT in the oXiris group was significantly shortened (P= 0.031 and 0.029, respectively). However, there were no significant differences in mechanical ventilation duration, intensive care unit (ICU) hospitalization time, total hospitalization time, ICU mortality, and in-hospital mortality. Conclusion: For patients with septic shock complicated by AKI, CRRT treatment with the oXiris hemofilter could effectively clear inflammatory cytokine levels and quickly correct hemodynamic disorders, thus accelerating the recovery of organ function.